Multiple Dermal Cylindroma - Lahiri Koushik; Sengupta Sujit R; Nath Torsha; Moitra Sudipata (Wolters Kluwer Medknow Publications, 1996)
A case of multiple dermal cylindroma in 22 year old males is reported. Although this disease has autosomal dominant mode of inheritance, no family history of similar illness was seen in our case.